The failure of integrated circuit: test and analysis - Hassan, Hasliza (Penerbit Uthm, 2019)
Failure analysis (FA) is an important function in the development and manufacturing of integrated circuits. It provides essential information for troubleshooting a complex device while ensuring reliability of a product. The objective of FA is to identify cause of failure and initiate corrective actions. Complex engineering knowledge is required in understanding the nature of a device failure, identifying the problem and subsequently providing a solution to avoid the failure again during the production of the device. FA identifies the causes of failure by analyzing stresses and other mechanisms causing failure. Device failure is defined as any non-conformance of the device to its electrical and/or visual/mechanical specifications. A failure mechanism usually leads to an identifiable change in a device. This chapter reveals the common techniques in troubleshooting IC and flow for identifying FA which consists of fault localization, de-processing, defect localization and inspection characterization. A failed component can provide important information to enhance the reliability of a device or product.